The Geocentric Cosmic Determination of Human Fingers and Toes and Socially Related Considerations - Struyf, Jef (Advances in Social Sciences Research Journal, 2025)
Numerical, proportional and structural accordances are determined between the classical geocentric cosmos, and the human fingers and toes. The three central fingers and toes accord to the twelve zodiacal constellations. The four “thumb-pinky” finger pairs and corresponding toe pairs accord to the four geocentric opposite planet pairs: Earth-Sun, Moon-Saturn, Mercury-Jupiter and Venus-Mars. Capita selecta of the actual social situation are analyzed. They concern: The gap between science and morality destroys nature, school education in question, support for a more creationistic approach, Ardakani’s analysis of western society and, is covid a result of a decline in the immune system?